PARADIGMA GURU DAN ORANGTUA TERHADAP PENERAPAN UNDANG-UNDANG PERLINDUNGAN ANAK DI SEKOLAH - Munawir, Ahmad (Al-Amwal : Journal of Islamic Economic Law, 2019)
Acts of violence involving students in schools have an impact on the pattern of teacher education and the mindset of parents of students on the education system with the child protection law. Therefore, this study aimsÂ atÂ describing the pattern of teacher education and the mindset of studentsâ€™ parents Â towards the application of child protection laws in schools. The research used descriptive qualitative research with library research. The results of the study shows that the child protection law has changed the pattern of teacher education and the mindset of parents of students towards the educational process that occurs in schools. The child protection law does not give the freedom for teachers to take decisive action and Â to give punishment to students; and it is used by the parents of students as a tool to criminalize teachers